Per un intelletto collettivo sociale. Piccole note per una teoria e una pratica dell’esodo - Bonomi, Aldo (Scienze del Territorio, 2018)
The article describes the leap of time that is affecting our society, with the transition from vertical society (which was based on the three polarities of capital, work with the state in the middle) to the horizontal one and then to the circular society, with its positive aspects such as the sharing economy and the negative ones such as the consequences on social composition as the centrality of the individual, the disintermediation, the dissolution of belonging mechanisms. To reconstruct a collective social intellect that can change the dominant model we need to start from the desire for proximity, inclusion, the many local experiences that put the alternative into practice and show that another type of development is possible, experiences and practices to network. The starting point is what remains of communities and their links with places, in their positive sense of communities of care and working in opposition to communities closed in themselves for localistic and rancorous drifts.